2020
DOI: 10.1186/s13287-020-01905-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local anesthetics on viability and differentiation of various adult stem/progenitor cells

Abstract: Background Local anesthetics (LAs) are widely used to control pain during various clinical treatments. One of the side effects of LAs, cytotoxicity, has been investigated in various cells including stem/progenitor cells. However, our understanding of the effects of LAs on the differentiation capacity of stem/progenitor cells still remains limited. Therefore, a comparative study was conducted to investigate the effects of multiple LAs on viability and multi-lineage differentiation of stem/progenitor cells that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Historically, lidocaine is considered to be one of the most cytotoxic local anesthetics. 9 Interestingly, ropivacaine did not reveal cytotoxic effects in concentrations up to 10 for brief and 1 mM for extended durations of exposure to ASCs. Mepivacaine may be used in concentrations up to 10 mM, but cytotoxic effects could occur.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Historically, lidocaine is considered to be one of the most cytotoxic local anesthetics. 9 Interestingly, ropivacaine did not reveal cytotoxic effects in concentrations up to 10 for brief and 1 mM for extended durations of exposure to ASCs. Mepivacaine may be used in concentrations up to 10 mM, but cytotoxic effects could occur.…”
Section: Discussionmentioning
confidence: 93%
“…3,8 However, they are considered cytotoxic in concentrations commonly found in ready-to-use medical products, which would render them impracticable when handling ASCs. [9][10][11][12][13] In addition, they are known to inhibit the differentiation capacity of mesenchymal stem cells (ie, in ASCs). 12,13 Thus, it was historically recommended to avoid using LAs when harvesting or transplanting ASCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, if the cell culture allows for a simple experimental approach, both the nutritional conditions (excess glucose in the culture medium) and the oxygen concentrations (ranging from hyperoxia to hypoxia in some parts of the flask if it is not agitated) often do not allow extrapolation of experimental results to clinical use. Moreover, our in vitro study doesn’t assess the impact of lidocaine on the microenvironment while it has been shown that local anesthetics could affect viability and differentiation capacity of adult stem/progenitor cells ( Kim et al, 2020 ; Kubrova et al, 2021 ). Those effects on mesenchymal stem cells could influence wound healing or tumor spreading after surgery ( Lucchinetti et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the amphiphilic nature of LA compounds, they partition into cell membranes and perturb the cell membrane matrix by modifying its physiochemical properties, such as permeability, fluidity, and electrostatic potential, which eventually affect membrane protein functions [8][9][10]. This indirect interaction model explains the mechanism of some local anesthetics and the associated toxic effects caused by LAs such as lidocaine, tetracaine, bupivacaine, and procaine [11,12]. Recently, several approaches were reported to analyze the effects of LAs on model-cell membranes.…”
Section: Introductionmentioning
confidence: 99%